Existence Results for a System of Fractional Differential Equations with Fractional Order Random Time Scale: Investigating the Uniqueness of Solutions for Non-linear Fractional Differential Equations on Fractional Order Random Time Scales (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper explores the extant of unique solution for a set of non-linear fractional differential equation with fractional order in capricious time lamina. The solutions are demonstrated by some basic fixed-point theory, Kooi’s, Rogers and Krasnoselskii-Krein conditions